Analisis Dampak Penyalahgunaan Wewenang terhadap Tindak Pidana Korupsi - Deby Shintawulan; Meilita Rizkynanda; Nouva Ayu Ramadhanti; Tries Ellia Sandari (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study aims to analyze the forms of abuse of authority that trigger corruption and the legal challenges in handling it. The method used is a qualitative approach with a case study, which will collect secondary data from related literature. The results of the study are expected to provide a better understanding of the impact of abuse of authority on governance and strategic steps to reduce corrupt practices. By increasing supervision and law enforcement, it is expected to contribute to efforts to eradicate corruption in Indonesia.